1977
DOI: 10.1055/s-0028-1097508
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATION ON SKIN–PHOTOSENSITIZING ACTIVITY OF VARIOUS KINDS OFPSORALEA

Abstract: The skin-photosensitizing activity of some coumavinic extracts has shown a correlation between the amount of psoralen and the extent of erythema produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Method 1 had been used in previous research and it represented an improvement (Innocenti et al, 1984) compared with simple methanolic extraction (Innocenti et al, 1977) which did not consider the possible occurrence, in plant material, of glycosylated precursors of furanocoumarins. However, method 1 proved to be unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Method 1 had been used in previous research and it represented an improvement (Innocenti et al, 1984) compared with simple methanolic extraction (Innocenti et al, 1977) which did not consider the possible occurrence, in plant material, of glycosylated precursors of furanocoumarins. However, method 1 proved to be unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…Psoralea bituminosa L., a very common Euro-Mediterranean species, formerly regarded as a poor natural source of the linear furanocoumarin psoralen and its angular isomer angelicin (Innocenti et al, 1977), showed high contents of bound furanocoumarins (Innocenti et al, 1993(Innocenti et al, , 1995 and therefore seemed to be a plant material that could be much more interesting than previously believed.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves, roots and seeds from control as well as irradiated plants collected at different developmental stages of P. corylifolia L. were investigated following the method of Innocenti et al (1977). Harvested biomass was dried in an oven at 55 C for 16 h and powdered by Wiley Mill (Model No.…”
Section: Extraction and Isolation Of Psoralenmentioning
confidence: 99%
“…Leaves, roots and seeds from control as well as irradiated plants collected at different developmental stages of Psoralea were investigated following the method of Innocenti et al (1977). Harvested biomass was dried in an oven at 55°C for 16 h and powdered by Wiley Mill (Model No.…”
Section: Extraction and Isolation Of Psoralenmentioning
confidence: 99%